CONTEMPORARY CHALLENGES IN CIVIL PROTECTION AND DEFENSE: DEVELOPMENT OF AN INTEGRATED MODEL FOR RAPID RESPONSE TO HYDROLOGICAL DISASTERS - Pimentel da Silva, Helton; Rodrigo de Sousa Fonseca, Ávila (Revista Gênero e Interdisciplinaridade, 2024)
The addressed problem is the need to enhance public policies and regulations in disaster management in Brazil, due to the increasing frequency and severity of these events. The hypothesis posits that integrating public policies with emerging technologies and community participation can significantly improve disaster management. The methodology involves a literature review of existing legislation, case study analysis, and the implementation of real-time hydrometeorological monitoring systems. Key results indicate that, despite advancements in prevention and mitigation policies, significant gaps remain in inter-institutional coordination and practical application of regulations. The main conclusion is that effective integration of public policies and emerging technologies is essential for risk reduction and the effective protection of vulnerable communities.